The management accounting practices in healthcare: The case of Czech Republic hospitals - Josef Krupička (European Financial and Accounting Journal, 2020)
The economic and demographical development in Europe in the last few decades has led to increased pressure on effectiveness in the healthcare industry. The growing importance of performance management in this industry resulted in agreater focus on management accounting practices capable of providing managers with relevant information to support their decision-making activity. This article presents the results of the survey examining the management accounting practice among the economic managers in public hospitals in the Czech Republic. The results from total of 60 respondents pointed out to management accounting practices being well established and rather conventional with the budgeting being the most relevant. Further results offer explanation of enabling factors of potential efficiency gains beneficial for managerial practice.
Keywords: I11; M41; 650; Management accounting practices; Healthcare performance management; Czech Republic